Pengaruh Pelatihan Karyawan dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Karyawan PT. Merek Indah - Yose Andre Sinuhaji (CV. Ulil Albab Corp, 2024)
One of the success factors of employees satisfaction in a company is the training employees and also leadership style of their superiors. Therefore a good company must pay attention to job satisfaction of employees. The aspect that should be noted are training and leadership style that support the improvement of employees satisfaction. The purpose of this research is to determine the positive and significant influence between training and leadership style towards of employees satisfaction of PT. Merek Indah and also to know which variable is more dominant between employees training and leadership style in influencing employees satisfaction at PT. Merek Indah. The analysis methods used in this research are quantitative analysis. The data used in this research were primary data and secondary data. The population of this research is 250 peoples and the sampling is using slovin formula to get samples become 154 peoples. The variables were measured by Likert scale. Data analysis technique in this research is multiple linear regressions.The results of this research stated that simultaneously training and cleadership style are influencing of employees satisfaction at PT. Merek Indah. Partially, training is influencing of employees satisfaction and leadership style is influencing of employees satisfaction at PT. Merek Indah